Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2967/jnumed.116.180380
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Net Influx Rate Images of 68Ga-DOTATOC and 68Ga-DOTATATE: Quantitative Accuracy and Improved Image Contrast

Abstract: Ga-DOTATOC and Ga-DOTATATE are radiolabeled somatostatin analogs used for the diagnosis of somatostatin receptor-expressing neuroendocrine tumors (NETs), and SUV measurements are suggested for treatment monitoring. However, changes in net influx rate () may better reflect treatment effects than those of the SUV, and accordingly there is a need to compute parametric images showing at the voxel level. The aim of this study was to evaluate parametric methods for computation of parametric images by comparison to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…In particular, Chen et al [35] reported that gradient-based tumor delineation method may be more accurate on Patlak Ki parametric maps compared to conventional static SUV images using magnetic resonance imaging as the GT. Furthermore, Llan et al [36] found that Ki images present better tumor-to-liver contrast compared with SUV images. Finally, Wangerin et al [37] assessed the variations during the PET imaging process using a series of linked simulations and found that Ki images were associated with superior receiver operating characteristic performance compared to SUV images.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Chen et al [35] reported that gradient-based tumor delineation method may be more accurate on Patlak Ki parametric maps compared to conventional static SUV images using magnetic resonance imaging as the GT. Furthermore, Llan et al [36] found that Ki images present better tumor-to-liver contrast compared with SUV images. Finally, Wangerin et al [37] assessed the variations during the PET imaging process using a series of linked simulations and found that Ki images were associated with superior receiver operating characteristic performance compared to SUV images.…”
Section: Discussionmentioning
confidence: 99%
“…We reconstructed the measurement data with a listmode-based three-dimensional maximum likelihood expectation maximization algorithm including self-normalization and resolution recovery (MLEM-RM) (Salomon et al 2012). The reconstruction algorithm grouped the data into 16 ordered subsets with 5 sub-iterations each, regularized with a relative difference prior with dynamic edge preservation parameters (Andreyev et al 2017, Nuyts et al 2002), and used a voxel pitch of 0.25 mm. Additionally, the reconstruction employs a likelihood-based rejection of inter-crystal detector scatter (Gross-Weege et al 2016) and applied corrections for attenuation, scatter and randoms.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we investigated the behaviour of BSREM in relation to OSEM regarding image quality in terms of noise, SNR, and SBR, with three non-18 F-FDG PET tracers regularly used in the clinical practice; gallium-68-DOTA-D-Phe 1 -Tyr 3 -octreotide ( 68 Ga-DOTATOC), carbon-11-acetate ( 11 C-acetate), and 18 F-fluoride. 68 Ga-DOTA-TOC is a radiolabelled somatostatin analogue used for imaging of neuroendocrine tumours [13][14][15]. 11 C-acetate, similarly to 11 C-and 18 F-choline, can be used for imaging of the cell membrane lipid metabolism that is typically increased in prostate cancer cells [16][17][18][19][20], and 18 F-fluoride is used for bone imaging, especially for the detection and monitoring of bone metastases in prostate cancer [21,22].…”
Section: Introductionmentioning
confidence: 99%